Effect of NADPH–cytochrome P450 reductase on all-trans-retinoic acid efficacy and cytochrome P450 26A1 expression in human myeloid leukaemia HL-60 cells. (1st July 2016) - Hu, Lei; Lv, Jin-Feng; Zhuo, Wei; Zhang, Cong-Min; Zhou, Hong-Hao; Fan, Lan
Abstract: Objectives: All-trans-retinoic acid (ATRA), a naturally occurring metabolite of vitamin A, has been shown to have great potential as an antitumorigenic drug to treat acute leukaemia by promoting cancer cell differentiation. Cytochrome P450 oxidoreductase (POR) is the only obligate electron donor for all of the microsomal cytochrome P450 enzymes including CYP26A1 which is highly specific for ATRA metabolism and efficacy in human myeloid leukaemia cells. In this study, we aimed to investigate the effect of POR on ATRA efficacy and CYP26A1 expression in human myeloid leukaemia HL-60 cells. Methods: Stably expressed POR and POR-RNAi HL-60 cell lines were established by transfecting POR overexpression or RNAi (RNA interference) vectors mediated by lentivirus. The protein expression of POR and CYP26A1 was examined by Western blot. The potential roles of POR on ATRA efficacy in HL-60 cells were explored by cell viability assay, cell cycle distribution, cellular differentiation and apoptosis analysis. Key findings: All-trans-retinoic acid treatment caused the expression of POR upregulation and CYP26A1 downregulation in dose- and time-dependent manners. POR overexpression decreased CYP26A1 expression in HL-60 cells. When POR gene was interfered, the downregulation of CYP26A1 expression by ATRA was abolished. In addition, POR overexpression in HL-60 cells significantly compromised ATRA-induced cell proliferation inhibition, cell cycle arrest, differentiation and apoptosis, whereas downregulation of POR significantly potentiated ATRA effects. Conclusions: Our study therefore suggested that POR played an important role in regulating ATRA efficacy and CYP26A1 expression in HL-60 cells.